Pendampingan Anak-Anak Madrasah Diniyah Ta’limiyah Nurul Hikmah melalui Kegiatan Pembelajaran di Desa Sahang, Kecamatan Ngebel, Kabupaten Ponorogo - Sudadi; Miftaku Ni'amah (Institut Agama Islam Sunan Giri Ponorogo, 2025)
This study aims to describe the form of learning support provided at the Nurul Hikmah Islamic Boarding School (Madrasah Diniyah Ta'limiyah Nurul Hikmah) in Sahang Village, Ngebel District, Ponorogo, and analyze its impact on children's religious understanding. The main problems faced by this Islamic boarding school are limited teaching staff, the dominance of lecture methods, and children's low understanding of religious material. The study used a qualitative method with an Asset-Based Community Development (ABCD) approach that focuses on optimizing local potential. Data were collected through observation, interviews, and documentation, then analyzed using the interactive model of Miles, Huberman, & Saldaña. The results show that support provided through a variety of active learning methods, the use of simple media, and collaboration with community leaders and parents. This approach resulted in improved Quranic reading skills, basic understanding of Islamic jurisprudence (fiqh), and children's worship practices. Furthermore, the children demonstrated higher learning motivation, improved religious attitudes, and courage in active participation. This study concludes that the local potential-based mentoring model has proven effective in increasing religious understanding while strengthening the role of Madrasah Diniyah as a center for non-formal religious education in rural areas.